A comparison study of heat-assisted Fe2+/persulfate and powdered activated carbon/persulfate wastewater pre-treatment for membrane fouling alleviation. (20th June 2023) - Shen, Yu; Mao, Xin; Liu, Fang; Yin, Wenjie; Shi, Wenxin; Zhang, Bing
Abstract: Heat/Fe 2+ /persulfate (PS) and heat/powdered activated carbon (PAC)/PS exhibit oxidation, coagulation, and adsorption effects, respectively. However, no studies have been conducted to discuss and compare the synergistic contribution to membrane fouling mitigation under thermal synergy. Herein, heat/Fe 2+ /PS and heat/PAC/PS systems were used to alleviate membrane fouling during municipal wastewater recycling in an aerobic granular sludge membrane bioreactor (AGMBR), and the effects of oxidation, coagulation, and adsorption on the membrane fouling mitigation were analyzed. The results showed that heat/Fe 2+ /PS and heat/PAC/PS effectively increased the filtration flux, decreased the fouling resistance, and maintained the membrane surface morphology. Compared to heat/PAC/PS, the heat/Fe 2+ /PS exhibited better control of membrane fouling owing to the generation of sulfate radicals and Fe 3+ . The non-radical effect is an important way to mitigate membrane fouling by heat/PAC/PS. Moreover, the pretreatment systems were effective in decomposition and removal of large-particle-size pollutants owing to their excellent oxidation capacity. According to the extended Derjaguin–Landau–Verwey–Overbeek theory, the heat/Fe 2+ /PS system had the higher energy barrier values of foulant–membrane (155.31 kT) and foulant–foulant (113.75 kT). The cake filtration and intermediate blocking models were the major mechanisms of membrane fouling, and efficient removal of chemical oxygen demand ( R 2 >0.93) and suspended solids ( R 2 >0.92) were beneficial to the membrane fouling mitigation. This study elucidates the differences in the mechanisms of heat/Fe 2+ /PS and heat/PAC/PS in mitigating AGMBR membrane fouling. Graphical abstract: Image 1 Highlights: Heat-assisted Fe 2+ /PS and PAC/PS were compared for membrane fouling mitigation. SO4 − . and Fe 3+ were responsible for the excellent heat/Fe 2+ /PS pretreatment. Heat/PAC/PS realized membrane fouling mitigation via the non-radical pathway. The pretreatment systems increased the repulsive effect of membrane and foulants. Membrane fouling mitigation was related to the efficient removal of COD and SS.